PENERAPAN MODEL PEMBELAJARAN SIMULASI PADA MATA PELAJARAN KEWIRAUSAHAAN SEBAGAI UPAYA PENINGKATAN MOTIVASI BELAJAR SISWA SMK NEGERI 7 YOGYAKARTA - dan M. Afif Syaifulloh, Fieka Praditaliana, Ova Tri Nugroho, (Pelita - Jurnal Penelitian Mahasiswa UNY, 2011)
The purpose of our study group was to determine whether the application of simulation models oflearning on the subjects of entrepreneurship to improve students’ motivation in SMK Negeri 7 Yogyakarta Class X.This research was a Classroom Action Research (CAR) conducted in several stages. Data collectionwas conducted by observing, interviewing and distributing questionnaires.With quantitative data which were then processed, it can be concluded that simulation model oflearning on the entrepreneurship subject could improve the learning motivation of the class X students inSMK Negeri 7 Yogyakarta.Keywords: simulation models, entrepreneurship, students’ motivation